1972
DOI: 10.1172/jci106820
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Renal Disease Induced by DNA—Anti-DNA Immune Complexes

Abstract: A B S T R A C T Rabbits immunized with ultraviolet-irradiated DNA (UV-DNA) produced high titers of serum antibody. This experimental model was studied to determine if injection of antigen (UV-DNA) intravenously into immunized animals would induce glomerulonephritis and proteinuria. Proteinuria was observed several days after the start of daily intravenous injections into immunized animals and was sustained as long as injections were continued, but fell to normal values after stopping antigen administration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1973
1973
1984
1984

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Native DNA (3) and DNA metabolites (16) have been demonstrated along the glomerular basement membrane and antibodies with specificities for nuclear antigens could be eluted from diseased SLE kidneys (2,3). Experimentally, kidney lesions and proteinuria have been induced in rabbits in which the presence of immune complexes of DNA and antibody have been repeatedly induced over a period of time (17). The immune mechanism leading to these lesions closely resembled the immune events which have been shown to operate in human SLE.…”
Section: Mice Skin Lesions Resembling Slementioning
confidence: 97%
“…Native DNA (3) and DNA metabolites (16) have been demonstrated along the glomerular basement membrane and antibodies with specificities for nuclear antigens could be eluted from diseased SLE kidneys (2,3). Experimentally, kidney lesions and proteinuria have been induced in rabbits in which the presence of immune complexes of DNA and antibody have been repeatedly induced over a period of time (17). The immune mechanism leading to these lesions closely resembled the immune events which have been shown to operate in human SLE.…”
Section: Mice Skin Lesions Resembling Slementioning
confidence: 97%
“…The appearance of free N-DNA antigen in serum previously containing anti-N-DNA antibody was found to correlate with an exacerbation of disease activity probably as a result of circulating immune complex formation (14). Evidence drawn from experimental models (34,35), antibody elution experiments (20,36), and the identification of N-DNA antigen along the glomerular basement membrane in SLE nephritis (20) provide strong arguments linking DNA-anti-DNA complexes with tissue injury in this disease. In our study, a good correlation existed between presence of N-DNA antibody and activity of disease as reflected by the degree of proteinuria.…”
mentioning
confidence: 99%
“…Approximately 100 lxg of dialyzed radiolabeled antigen in a volume of 100 ,l was separated on the gradient as a purification step before being used in the radioimmunoassay. Gradients were centrifuged at 35 can be separated from free sNP by this technique since sNP is soluble in 50% saturated ammonium sulfate solutions, whereas sNP-antibody complexes are insoluble. Sera were decomplemented by incubation at 560C for 30 min and diluted 1: 10 in DSC, pH 7.2.…”
mentioning
confidence: 99%
“…Recent studies have shown lung disease seems to be specifically associated with MCTD but not SLE patients (Shirai et al, 2012;Watanabe et al, 2012;Gunnarsson et al, 2013). By contrast, renal disorders have long been a characteristic prevalent in SLE but not the MCTD population (Everett and Harrell, 1956;Natali et al, 1972;Cavagna et al, 2013;Lin et al, 2013). The fact that independent studies have described that SLE and MCTD patients are associated with malfunction of different organs highlights the relevance of the recognition of MCTD concept as a clinical tool to identify patients that could develop lung disease as oppose to kidney malfunction, for example.…”
Section: Mixed Connective Tissue Disease (Mctd) Is One Of the Most Comentioning
confidence: 99%
“…Second, the concept of MCTD has clinical relevance since malfunction of vital organs has been reported to be prevalent in this syndrome when compared to SLE, for example (Everett and Harrell, 1956;Natali et al, 1972;Shirai et al, 2012;Watanabe et al, 2012;Gunnarsson et al, 2013). Third, new classification rules with significant power to distinguish between SLE and MCTD patients need to be developed given that available classification criteria sets were designed to identify either SLE or MCTD subjects but not to segregate between these two autoimmune disorders (Sharp, 1987;Kasukawa et al, 1988;Kahn et al, 1991;Amigues et al, 1996;Hochberg et al, 1997;Petri et al, 2012).…”
Section: Mixed Connective Tissue Disease (Mctd) Is One Of the Most Comentioning
confidence: 99%